Applications of ALS (Airborne Laser Scanning) data to Forest Inventory. Experiences with pine stands from mountainous environments in Spain. (January 2019) - Pascual, C; Mauro, F; García-Abril, A; Manzanera, J A
Abstract: The estimation of forest using Airborne Laser Scanning (ALS) data as auxiliary information has advanced substantially after more than three decades of studies. Numerous experiences have confirmed the potential of ALS data for the estimation of aggregated attributes such as volume, basal area or dominant height, and have developed methodologies to obtain predictions at a plot level. This paper summarizes, interrelates and built new conclusions of different analyses on estimation of forest variables assisted with ALS data, in pine forests in the mountain systems of central Spain: Pinus sylvestris L., Pinus nigra Arn. and Pinus pinaster Ait. These studies also consider: 1) forest with different levels of heterogeneity, 2) different methodologies and protocols and 3) different spatial disaggregation units for forest inventory and management. All these factors make it difficult to directly compare certain results. However, the large amount of information provided by these studies allows having comparative examples, and providing references for future inventories. Other results regarding more methodological aspects, such as the sampling methods, plot sizes or ALS point densities can be extrapolated as procedures on a regional or local scale for the estimation of different stand features (species, basal area, dominant height, volume, etc.).